The Problems of Islands - Quentin-Baxter, Alison (Victoria University of Wellington Law Review, 2000)
The paper reproduced in this article was given at a public seminar held at Waitangi, Chatham Islands, on 5 and 6 February 1995 to discuss "Island Development and its Future". In it Alison Quentin-Baxter compares the legal situation of the Chatham Islands with the past and present situations of the Cook Islands, Niue and Tokelau, concluding that the Chatham Islands are not a non-self-governing territory but are an integral part of New Zealand. She then discusses the consequences of this status for the Chatham Islands, particularly in relation to the fish resources of their surrounding waters and suggests that the goal of self-government is not a realisable one. She proposes instead a dialogue with New Zealand Ministers in an effort to reach acceptable, pragmatic solutions, perhaps involving some legislative changes of a constitutional nature giving greater authority to local government in the Chatham Islands or modifying the application there of some Acts of Parliament, so as to take account of the practical problems that offshore islands experience.